2016
DOI: 10.1111/acer.13048
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake During Pregnancy and Offspring's Atopic Eczema Risk

Abstract: Alcohol consumption during pregnancy might have an effect on developing atopic eczema in offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…In a recent report evaluating a Japanese cohort, maternal alcohol intake during pregnancy significantly increased the risk of atopic eczema before age 3 and before age 5. 49 These data are in agreement with other authors, who demonstrated an increased risk of atopic dermatitis in early infancy 50 and during the first 7 years of life in alcohol-exposed offspring. 51 Nevertheless, the data on foetal alcohol’s effect on the development of asthma is less convincing.…”
Section: Foetal Alcohol Exposure and Risk Of Adverse Pulmonary Outcomessupporting
confidence: 93%
See 1 more Smart Citation
“…In a recent report evaluating a Japanese cohort, maternal alcohol intake during pregnancy significantly increased the risk of atopic eczema before age 3 and before age 5. 49 These data are in agreement with other authors, who demonstrated an increased risk of atopic dermatitis in early infancy 50 and during the first 7 years of life in alcohol-exposed offspring. 51 Nevertheless, the data on foetal alcohol’s effect on the development of asthma is less convincing.…”
Section: Foetal Alcohol Exposure and Risk Of Adverse Pulmonary Outcomessupporting
confidence: 93%
“…In the Japanese cohort, offspring exposed to maternal alcohol demonstrated a 2 fold, albeit non-significant (p=0.058) increased risk of asthma before age 3, suggesting further studies are warranted. 49 However, in a large Norwegian cohort, maternal alcohol use during pregnancy had no significant effect on asthma at age 3 or age 7, 52 while a study of newborns in Copenhagen demonstrated no effects of alcohol exposure on infant lung function testing at one month of age. 53 …”
Section: Foetal Alcohol Exposure and Risk Of Adverse Pulmonary Outcomesmentioning
confidence: 93%
“…Two older case‐control studies obtained the lowest scores, both with 8 out of a possible 19. In comparison, the highest score was obtained by Wada et al with 16 out of a possible 19. Items commonly insufficiently addressed included the following: reporting on the representativeness of study participants (items 11 and 12), mentioning if an attempt was made to blind those measuring the main outcomes (item 15), and including a power calculation to assess sample size validity for detecting a significant difference between PAE and control group, if it occurs (item 27).…”
Section: Resultsmentioning
confidence: 77%
“…Most recently, Carson et al analyzed data from the Copenhagen Study on Asthma in Childhood, which recruited children born to women with a history of asthma. The three remaining longitudinal studies were from Norway, the United Kingdom (UK), and Japan . The Norwegian study assessed outcomes from the Mother and Child Cohort Study, which recruited pregnant women and followed up children until 7 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation